Cellulose acetate obtained from Schizolobium parahyba (vell.) blake wood - Allesi, Leticia Sant'Anna (2021)
Currently, non-biodegradable polymers are produced on a large scale and cause several environmental problems, especially due to their low degradation. Cellulose acetate is a non-toxic, low-flammable and low-cost polymer, playing an important environmental role. The objective of this study was to synthesize cellulose acetate membranes from Schizolobium parahyba wood (“guapuruvu”) with particles sizes of 20 and 60 mesh. The materials were submitted to acetosolv pulping, bleaching and acetylation to produce the acetates. The yields and the degree of substitution were found. The fibers were chemically characterized and the samples obtained at each processing step were analyzed by FTIR. It was possible to prepare acetates from both granulometries wood. The FTIR analysis showed changes on the samples’ bands, indicating that the chemical processes were efficient. Cellulose acetate obtained from the 60 mesh material presented a higher degree of substitution (2.74 ± 0.12) when compared to the 20 mesh acetate (2.59 ± 0.13), showing that the particle size of the material influenced on the efficiency of the acetylation reaction. DMA tests have demonstrated that the 60 mesh membrane has higher flexibility and transparency when compared to the 20 mesh membrane.